(3CKQ HQfGeL bGFe Ydi fehPL CHYGO GdJYde ai JfejI YGOGJ GdYbd GdeYQajI h GdhLOGfjI GdEjLGHjI dOi GdeJahbjf h GdYGOjjf ef JdGejP GdMdbI GdEYOGOjI (B= s The effect of a program for dimensions of learning model for developing positive cognitive and affective habits of mind for excelled and average prep stage pupils - (3RjRi EHQGgje CMeO eTGdis; (3CSeGA Jhajb eHQhc (B: s; (3LGHQ YHOGdMejO LGHQ (B: s; (3efi MSf HOhi (B: s ((3GdbGgQI (B: s (3RjRi EHQGgje CMeO eTGdi (B: s, 2018)
(3gOaJ GdOQGSI GdMGdjI HMK CKQ HQfGeL bGFe Ydi fehPL CHYGO GdJYde deGQRGfh ai JfejI YGOGJ GdYbd GdeYQajI h GdhLOGfjI GdGjLGHjI dOi GdJdejPGJ GdeJahbGJ h GdYGOjGJ HGdeQMdI GdGYOGOjI(B: (3h JhUdJ GdOQGSI Edi hLhO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWGJ OQLGJ GdeLehYI GdJLQjHjI h GdVGHWI ef GdYGOjGJ(B: (3h GdeJahbGJ ai YGOGJ GdYbd GdeYQajI h GdhLOGfjI (B((3GdOQLGJ GdaQYjI h GdOQLI GdcdjI(B) (3ai GdJWHjb GdHYOi ai GJLGg GdeLehYI GdJLQjHjI(B: (3ceG Cf MLe JCKjQ GdHQfGeL HGdfSHI deLehYI GdeJahbGJ HdZ (B(88%) (3h gh MLe JCKjQ cHjQ(B: (3h HdZ (B(77%) (3HGdfSHI deLehYI GdYGOjGJ(B: (3JhUj GdHGMKI HGdGSJaGOI ef fehPL CHYGO GdJYde ai GdYedjI GdJYdjejI h OeL JYdje YGOGJ GdYbd Vef GdefGgL GdOQGSjI deG dgeG ef CKQ cHjQ ai JfejI GdLhGfH GdeYQajI h GdhLOGfjI dOi GdJdGejP(B: (3Hd JfejI GdTNUjI ccds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe Yde GdfaS GdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3YGOGJ GdYbd GdeYQajI GdGjLGHjIs; (3YGOGJ GdYbd GdhLOGfjI GdGjLGHjIs; (3fehPL CHYGO GdJYde deGQRGfhs